RETRACTED: Does industrial up-gradation, environment regulations, and resource allocation impact on foreign direct investment: Empirical evidence from China - Xiong, Jiacai; Chen, Linghong (Frontiers in Psychology, 2022)
Because of China's tremendous increase in foreign direct investment (FDI) over the past two decades, this method of internationalization has become increasingly significant for companies worldwide. Heavy industry's dominant role in China's industrial structure must be modernized to ensure the country's long-term growth and prosperity. There are 30 provinces in China covered by this dataset, which dates back from 2005 to 2018. AMG and CCE-MG estimations demonstrate that China's industrial upgrading and resource allocation considerably impact FDI inflows. FDI inflows appear to be negatively affected by environmental rules. The results show that environmental regulations have not had the expected effect on FDI in China without the participation of other stakeholders. For the selected panel, results from the control variable show that population aging reduces foreign direct investment inflows, whereas economic growth increases FDI inflows. According to our findings and those of the empirical study, we make some policy proposals to help Chinese provinces attract more foreign direct investment by encouraging and upgrading the screening of such investments.